2020
DOI: 10.3390/ijfs8020032
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for the Challenge of Banks 4.0? Designing a Roadmap for Banking Systems in Industry 4.0

Abstract: The purpose of the present paper is to provide an advanced overview of the practical applications of Banking 4.0 in Industry 4.0. This paper examines the technology trends in the Fourth Industrial Revolution and identifies the key indicators behind the creation of a strategic map for the fourth-generation banks and their readiness to enter Industry 4.0. This paper examines a systematic review of fully integrated Banking 4.0 and the application of the technologies of Industry 4.0 and illustrates a distinct patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 79 publications
0
37
0
3
Order By: Relevance
“…It was estimated that by 2025, the value of SE would be $335 billion in 2025 (Yaraghi & Ravi, 2017) and this forecast was on the track of becoming a reality. Moreover, Mehdiabadi et al (2020) suggested that currently, FinTech is seen as a good platform for implementing ideas based on the sharing economy and crowdfunding. But unfortunately, the COVID-19 outbreak happened and shattered the entire economic system.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that by 2025, the value of SE would be $335 billion in 2025 (Yaraghi & Ravi, 2017) and this forecast was on the track of becoming a reality. Moreover, Mehdiabadi et al (2020) suggested that currently, FinTech is seen as a good platform for implementing ideas based on the sharing economy and crowdfunding. But unfortunately, the COVID-19 outbreak happened and shattered the entire economic system.…”
Section: Introductionmentioning
confidence: 99%
“…Our research study provides an additional contribution to the existing literature such as: Spulbar and Nițoi (2012), , Spulbar and Niţoi (2013), Spulbar and Birau (2019), Mehdiabadi et al (2020) and many others.…”
Section: Literature Reviewmentioning
confidence: 75%
“…According to , a sustainable development-based approach has significant implications for low and middle-income countries (emerging), considering their main characteristic features such as: demographic dynamics, high degree of poverty, poor quality education, migration, environmental degradation, social inequality, high levels of urbanization, health system deficiencies, rapid technological change, and unsustainable economic growth [105]. Mehdiabadi et al (2020) argued that considering current challenges, the global economy is very dynamic and constantly changing, so innovation and technological development represent essential aspects in regards to a sustainable perspective [106].…”
Section: Discussionmentioning
confidence: 99%